The methane imperative - Shindell, Drew; Sadavarte, Pankaj; Aben, Ilse; Bredariol, Tomás de Oliveira; Dreyfus, Gabrielle; Höglund-Isaksson, Lena; Poulter, Benjamin; Saunois, Marielle; Schmidt, Gavin A.; Szopa, Sophie; Rentz, Kendra; Parsons, Luke; et al. (Frontiers in Science, 2024)
Anthropogenic methane (CH4) emissions since 1850-1900 are responsible for around 65% as much warming as carbon dioxide (CO2) has caused to date, and large reductions in methane emissions are required to limit global warming to 1.5C or 2C. However, methane emissions have been increasing rapidly since ~2006. This study shows that emissions are expected toWritingoriginal draft (mandatory criteria to qualify for authorship)Preparation, creation and/or presentation of the published work, specifically writing the initial draft (including substantive translation).